Effect Of Organizational Culture And Leadership On Student Association Member Loyalty At The Faculty Of Economics And Business UNSIKA - Laela Rahma Adila; Cecep Hermana (BIMA Journal (Business, Management, & Accounting Journal), 2026)
Purpose: This research aims to analyze the effect of organizational culture and leadership on member loyalty in the Student Association of the Faculty of Economics and Business, Universitas Singaperbangsa Karawang, considering that member loyalty is essential for organizational sustainability. Methodology: A quantitative research using a survey method on 50 respondents as a sample, and the data was analyzed using multiple linear regression analysis. Results: The findings indicate that organizational culture and leadership have significant partial and simultaneous effects on member loyalty. Findings: Organizational culture and leadership jointly explain 60.7% of the variance in member loyalty. Novelty & Originality: This study highlights the synergy between organizational culture and leadership in shaping loyalty within student organizations. The research specifically examines the context of HIMA in FEB UNSIKA using indicators aligned with student organizational dynamics. Conclusions: A participatory organizational culture and effective leadership significantly enhance member loyalty. Type of Paper: This paper is a research paper.